Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Yorozu Automotive Indonesia - Fahira, Salma Ridha; Suroso, Suroso; Anggela, Flora Patricia (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The aim of this research is to determine the influence of compensation and discipline on employee performance partially and simultaneously. This study uses a quantitative approach. This population is employees of PT. Yorozu Automotive Indonesia, located in the Mitra Karawang Industrial Area, has 176 employees. A sample of 122 people was taken because the Slovin formula was used. The data collection method uses a questionnaire and analysis tools use SPSS using multiple linear regression analysis. The results of the research show that there is a partial influence between the Compensation variable (x1) on Employee Performance (y) with a calculated t value > t table (9.733> 1.979) and there is a partial influence between the Work Discipline variable (x2) on employee performance (y) with a value t count > t table (4.776> 1.979) and there is a simultaneous influence between the variables compensation (x1) and Work Discipline (x2) on Employee Performance (y) with a value of F count > F table (95.044> 3.07), namely 61, 5%.